Sistem Informasi Log Book Harian Peserta Magang Pada Dinas Kominfo Kota Semarang - Yunus Yunus Anis; Sri Mulyani; Hersatoto Listiyono; Sekar Ayu Ningtyas (Bulletin of Information Technology (BIT), 2022)
Log book is a record book of important events in the management, operation, and navigation of ships. In simple terms, the log book is used by apprentices to record daily or daily / time activities carried out during internships. It can also train apprentices to be disciplined and orderly to record information related to improving the skills of apprentices in the field. The use of the daily log book of apprentices within the Ministry of Communication and Informatics is intended for daily reporting of the activities that have been carried out by apprentices as well as a data recap for the Office of Communication and Information Technology in evaluating whether the learning activities provided are in accordance with the needs of the apprentices or not. By utilizing the website application as an online medium, it will help the reporting process go faster. The electronic log book system has the advantage that research activities can be monitored at any time. The software development method used is waterfall which is built using the PHP programming language, CSS and Bootstrap Framework, as well as database processing using MySQL. The method of testing is done by blackbox, namely testing is done by testing the software in terms of functionality. The results of the research, namely the Internship Diary Log Book Information System at the Semarang City Communication and Informatics Service can help interns to make reports quickly.